Association between thoracolumbar fascia injury and residual back pain following percutaneous vertebral augmentation: a systematic review and meta-analysis - Ahmed Mohamed, Abdiaziz; Xuyang, Xu; Zhiqiang, Zhang; Chen, Jianghu (Frontiers in Endocrinology, 2025)
ObjectiveTo evaluate the association between a thoracolumbar fascia injury (TLFI) and the development of residual back pain (RBP) following percutaneous vertebral augmentation (PVA).BackgroundOsteoporotic vertebral compression fractures (OVCF) commonly affect elderly individuals and those with osteoporosis, leading to pain and limited mobility. Percutaneous vertebral augmentation provides immediate pain relief and stabilization of the fractures. However, some patients experience residual pain after the treatment. Although recent studies have suggested a potential association, the role of TLFI in RBP remains inconclusive. The aim of this meta-analysis was to evaluate this association.MethodsA thorough search was performed across the PubMed, Medline, Embase, Web of Science, and Cochrane Library databases from inception to 31 December 2024 to identify studies examining the link between TLFI and RBP following PVA. A random-effects model was used to combine the outcome data to account for the potential heterogeneity among the included studies.ResultsThis meta-analysis included 13 studies with a total of 4,542 participants and a TLFI incidence rate of 28%. Univariate analysis indicated that patients with a TLFI were significantly more likely to develop RBP compared to those without a TLFI, with an odds ratio (OR) of 4.19 (95% CI: 2.49 to 7.05, I² = 76.9%). The sensitivity analysis identified two studies as significant influential outliers that contributed to the majority of the observed heterogeneity. Excluding these studies resulted in an OR of 4.62 (95% CI: 3.61 to 5.92, I² = 0%). The multivariate analysis confirmed a strong association between TLFI and RBP after adjusting for confounders and other risk factors, with an OR of 4.57 (95% CI: 3.28 to 6.37, I² = 81.5%). The sensitivity analysis identified three studies as significant influential outliers, and excluding them resulted in an OR of 4.79 (95% CI: 3.76 to 6.11, I² = 0%) with no heterogeneity. This finding further confirms the association with a more homogenous overall effect estimate.ConclusionThe pooled effect size of both univariate and multivariate analyses consistently demonstrated that a TLFI significantly increased the risk of developing RBP after PVA regardless of other related risk factors. Recognizing fascia injury as a potential source of postoperative pain in clinical practice could enhance the care of these patients and mitigate postoperative pain.